2018
DOI: 10.21815/jde.018.032
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Cell Biology to Dental Students with a Project‐Based Learning Approach

Abstract: Although the discipline of cell biology (CB) is part of the curricula of predoctoral dental schools, students often fail to recognize its practical relevance. The aim of this study was to assess the effectiveness of a practical-theoretical project-based course in closing the gaps among CB, scientific research, and dentistry for dental students. A project-based learning course was developed with nine sequential lessons to evaluate 108 undergraduate dental students enrolled in CB classes of a Brazilian school of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 34 publications
1
32
0
5
Order By: Relevance
“…Project-based learning, one-onone tutoring, and cooperative group work can encourage individual interest (Mitchell, 1993;Schraw and Dennison, 1994;Hoffmann, 2002;Hidi and Renninger, 2006). Project-based learning in particular is a popular approach within biology and the life sciences, generally exhibiting improvements in learning and transfer gains compared with non-project based approaches (see Beach and Alvarez, 2015;Berchiolii et al, 2017;Costa-Silva et al, 2018). For example, a project-based learning approach in cell biology improved dental students' ability to recognize the relevance of cell biology to dentistry and improved their ability to produce reports that focused on scientific methodology and its relationship to dentistry (Costa-Silva et al, 2018).…”
Section: Interestmentioning
confidence: 99%
“…Project-based learning, one-onone tutoring, and cooperative group work can encourage individual interest (Mitchell, 1993;Schraw and Dennison, 1994;Hoffmann, 2002;Hidi and Renninger, 2006). Project-based learning in particular is a popular approach within biology and the life sciences, generally exhibiting improvements in learning and transfer gains compared with non-project based approaches (see Beach and Alvarez, 2015;Berchiolii et al, 2017;Costa-Silva et al, 2018). For example, a project-based learning approach in cell biology improved dental students' ability to recognize the relevance of cell biology to dentistry and improved their ability to produce reports that focused on scientific methodology and its relationship to dentistry (Costa-Silva et al, 2018).…”
Section: Interestmentioning
confidence: 99%
“…[16][17][18] Other studies of these pedagogical techniques in dental curricula have found improved results in terms of students' understanding of the concept, relected in their academic performance. [19][20][21] However, implementation of these pedagogical techniques and their combination in postdoctoral dental programs in subjects like biostatistics and research methodology has not previously been explored. Therefore, the aim of this study was to compare postgraduate dental students' academic performance using two teaching methodologies (video-based learning and blended module-based learning) in a biostatistics and research methodology course in a master's program at a dental college in India.…”
mentioning
confidence: 99%
“…The introduction of project-based learning in microbiology curriculum reform enhanced the consolidation of theory knowledge, improved experimental skills, cultivated innovative scientific thinking, and strengthened the awareness of oral health in a study from Japan [26]. In another study, this time focusing on teaching cell biology to dental students, the authors found that students receiving the project-based learning approach were more familiar with the importance methodological issues, were able to produce written reports of higher quality, better understood the relationship between their subject and the practice of dentistry and were better able to recognize the relevance of biomedical investigation as compared to control students receiving the traditional lecture-based approach [23]. There are few standardized, well designed controlled trials investigating the effectiveness of problem-or project-based learning in dentistry [27] and, to the best of our knowledge, this is the first study of its kind to investigate the outcomes of project-based learning on non-laboratoryskills elements of microbiology teaching.…”
Section: Discussionmentioning
confidence: 99%
“…The development of creative, engaging programs to stimulate learning of key, contemporary issues in modern dentistry programs is of the highest importance. Multiple authors describe the benefits of student engagement in self-driven research projects with key outcome goals as a strategy to enhance the learning process [22][23][24]. The Microbiology and Virology curriculum is particularly susceptible to such enhancement as students traditionally find the subject complex, dry and difficult to apply to their activity as a dentist.…”
Section: Discussionmentioning
confidence: 99%